ESG Outcasts: Study of the ESG Performance of Sin Stocks - Gabriel Paradis (Sustainability, 2021)
Certain economic actors are considered by many as involved in or associated with an activity that is considered unethical or immoral, such as the producers of tobacco, alcohol and firearms (often referred to as sin stocks). In an environment in which stakeholders are increasingly interested in sustainable development and corporate social responsibility, it is important to understand how firms respond to these issues which divide public opinion. Our study compares the environmental, social and governance (ESG) performance for a targeted sample of 79 sin stocks and a control group of comparable firms. We observe that sin stocks have a lower overall ESG performance as well as for each of the three ESG pillars, and that this difference is more significant in relation to governance and some key social and environmental issues for which sin stocks could have compensated risk exposure with responsible management practices. In other words, our results demonstrate that sin stocks are exposed to more severe ESG issues and consistently lack the necessary practices to mitigate these issues. Our study provides relevant insights into the informativeness of ESG scores to distinguish firms (and sectors) investing in management practices that offset ESG risk exposure.